The influence of instructional leadership and organizational commitment to elementary schools teacher performance in Central Lombok - Nazim, Muhamad; Agung, Anak Agung Gede; Yudana, I Made; Dantes, Kadek Rihendra (International research journal of management, IT and social sciences, 2023)
The research objective was to determine the effect of instructional leadership and organizational commitment on the performance of elementary school teachers in the Central Lombok District. The research design is descriptive and quantitative with a research sample of 361 teachers based on Morgan's theory which is corrected using the Warwick and Lininger formulas. Data collection techniques using questionnaires were then analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The research results are; (1) Instructional Leadership has a direct positive and significant effect on Organizational Commitment as indicated by the results of the T-Statistic 87.320 and P-Values 0.000; (2) Instructional leadership has a direct positive and significant effect on teacher performance as indicated by the results of the T-Statistic 17.207 and P-Values 0.000; (3) Organizational Commitment has a direct positive and significant effect on teacher performance as indicated by the results of the T-Statistic 9.620 and P-Values 0.000; (4) Instructional Leadership has a positive and significant indirect effect on teacher performance through Organizational Commitment shown by the results of T-Statistics 9.429 and P-Values 0.000. The findings of this study are that Instructional Leadership has a direct effect on Organizational Commitment and Teacher Performance.